A deployment value model for intrusion detection sensors - Shaikh, Siraj A.; Chivers, Howard; Nobles, Philip; Clark, John A.; Chen, Hao (Springer, 2010)
The value of an intrusion detection sensor is often associated with its data collection and analysis features. Experience tells us such sensors fall under a range of different types and are diverse in their operational characteristics. There is a need to examine some of these characteristics to appreciate the value they add to intrusion detection deployments. This paper presents a model to determine the value derived from deploying sensors, which serves to be useful to analyse and compare intrusion detection deployments.